Postoperative hyperammonemic encephalopathy due to unexpected constipation in a patient with hyperornithinemia-hyperammonemia-homocitrullinuria syndrome: a case report - Haruka Tachibana; Nobuhiko Ohashi; Gaku Okumura; Ryusuke Tanaka; Satoshi Fuseya; Sayako Gotoh; Takashi Ishida; Sari Shimizu; Mikito Kawamata; Satoshi Tanaka (JA Clinical Reports)
Abstract Background Hyperornithinemia-hyperammonemia-homocitrullinuria (HHH) syndrome is a rare autosomal recessive urea cycle disorder associated with a high risk of exacerbation of hyperammonemia during the perioperative period. Here, we describe an adult patient with HHH syndrome who developed hyperammonemic encephalopathy secondary to postoperative constipation. Case presentation A 52-year-old patient with HHH syndrome underwent intrathecal baclofen pump insertion for lower limb spasticity under general anesthesia. The surgery was uneventful, without any increase in serum ammonia levels. However, after surgery, he was constipated, and on postoperative day (POD) 3, he fell into a coma with an exacerbation of hyperammonemia (894 µg/dL). After administering a glycerin enema, he defecated, leading to a rapid decrease in serum ammonia levels to 165 µg/dL. He regained consciousness, and serum ammonia levels remained stable as long as he defecated. Conclusions We suggest strict management of defecation during the perioperative period to prevent hyperammonemia in patients with HHH syndrome.